My reflections on the Blackwell-Tapia prize - Richard Tapia (Mathematical Biosciences and Engineering)
The first two sections of this paper entitled The Conference and The History are taken directly from the webpage of the NSF sponsored Mathematical Sciences Institutes [1]. In the third section I share personal views.